Proses Pembelajaran Suku Anak Dalam di Desa Pauh Menang Kecamatan Pamenang Kabupaten Merangin Provinsi Jambi - Uying Hapid Alatas; Sri Utami; M. Syukurman (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research is motivated by the education of the Anak Dalam Tribe, where currently SAD is also very concerned about their education for the life to come. This is the basis of the research, namely how the learning process for SAD children is and what methods are used in the SAD teaching and learning process. This study aims to describe and reveal the learning process for the inner tribe in Pauh Menang Village, Pamenang District, Merangin Regency. This research uses a qualitative case study approach. To describe the SAD learning process, the data collection techniques used were observation, interview and documentation techniques. Research informants are SAD administrators, tribal chiefs and tutors who educate, and purposive sampling technique is used. Data analysis is done by describing data, reducing data, classifying data, analyzing data units, interpreting data, and drawing conclusions. The technique of guaranteeing the validity of the data is done by checking the degree of trustworthiness of the data through different times and tools. The results show that the SAD learning process in Pauh Menang Village is the learning process that does not use lesson plans and does not use the final results of learning. Before learning begins, they are accustomed to praying, first one of the students comes forward to lead the prayer, and before the teaching and learning process begins, the tutor uses an approach to students so that when they study they are not afraid or embarrassed. When the teaching and learning process takes place, not all students understand what is taught by the tutor, here the tutor teaches one by one to these students and they want to follow it. After learning is complete, students conclude the learning equipment and one of the students comes forward to lead the prayer home. After praying, the children went home and kissed the hand of the tutor who taught them.